The effects of three different low-volume aerobic training protocols on cardiometabolic parameters of type 2 diabetes patients: A randomized clinical trial - Gentil, Paulo; Silva, Lucas Raphael Bento e; Antunes, Daniela Espíndola; Carneiro, Luciana Barbosa; de Lira, Claudio Andre Barbosa; Batista, Gislene; Oliveira, Jordana Campos Martins de; Cardoso, John Sebastião; Souza, Daniel CostaCosta; Rebelo, Ana Cristina Silva (Frontiers in Endocrinology, 2023)
Objective: To investigate the effects of different types of aerobic training protocols on cardiometabolic variables in patients with type 2 diabetes mellitus (T2DM). Methods: Forty-four patients with T2DM were randomized in three different exercise protocols, equated by work performed. Exercise intensity was based on the speed corresponding to the maximum oxygen consumption (vV ̇O2max). Moderate intensity continuous training (MICT) involved 14 continuous minutes at 70% of vV ̇O2 max; high-intensity interval training involving short intervals (S-HIIT) consisted of 20 bouts of 30 seconds at 100% of vV ̇O2max with passive recovery of 30 seconds; high-intensity training involving long intervals (L-HIIT) consisted of 5 bouts of 2 minutes at 100% of vV ̇O2max with passive recovery of 2 minutes. Training protocols were performed on a motorized treadmill. Cardiometabolic evaluations were performed before and after eight weeks and involved glycated hemoglobin (Hb1Ac), total cholesterol, triglycerides, resting systolic blood pressure (SBP), resting diastolic blood pressure (DBP), resting heart rate (resting HR) and maximum oxygen consumption (V ̇O2max)]. Results: L-HIIT significantly reduced HbA1c (median difference = -1.7% [95% CI = -2.8; -0.8], p = 0.001; rB = -0.88 [broad effect]) and resting SBP (mean difference = -12 mmHg [CI95% [-22; -3], p = 0.012; d = -0.74 [medium effect]). While no changes were observed after the MICT and S-HIIT interventions. There was a significant increase in V ̇O2max after L-HIIT (median difference = 3.5 ml/kg/min [95% CI = 2.5; 4.5], p = 0.001; rB = 1.00 [broad effect]) and S-HIIT (median difference = 3.5 ml/kg/min [CI95% = 3.0; 4.5], p = 1.000; rB = 1.00 [broad effect]), but not after MICT. Conclusion: All exercise protocols improved at least one of the variables analyzed However, the most evident benefits were after the high intensity protocols, especially L-HIIT. Based on this, L-HIIT seems to be especially recommended for controlling cardiometabolic risks in patients with T2DM.